Survey on the Knowledge Base of EFL Pre-service Teachers for Phonics Instruction - Minjie, Chen (Human Resource Management Academic Research Society, 2022)
Phonics which refers to the letter-sound relationship originates in English speaking countries. Phonics instruction is part of early reading instruction. Based on previous literatures, the most suitable one for EFL students is synthetic phonics instruction approach. Since 2011, phonics is required by National English Curriculum in China, literatures indicated that in the actual teaching activities, it is hard to implement phonics instruction, regardless of phonics instruction approaches. The rationale for this is that the in-service teachers and pre-service teachers are short of subject matter content knowledge. Very few studies are conducted to look into in-service EFL teachers and pre-service EFL teachers’ knowledge base to teach phonics. To bridge the gap, this study aims at providing preliminary descriptive data via a survey on pre-service EFL teachers’ knowledge base to teach phonics. To attain this goal, 104 pre-service EFL teachers ranging from the first academic year to the fourth academic year are selected via random sampling technique to fill in the survey. The findings indicate their weak knowledge base for phonics instructions. This study hopes to provide empirical information for policy makers or researchers to look into this matter to take some measures to prepare pre-service EFL teachers to teach phonics in order to promote the implementation of phonics instruction in EFL context in China.